Effect of cold plasma on essential oil content and composition of lemon verbena. Issue 4 (22nd February 2019) - Ebadi, Mohammad‐Taghi; Abbasi, Soleiman; Harouni, Amir; Sefidkon, Fatemeh
Abstract: Cold plasma is known as a novel nonthermal processing method for decontamination of medicinal and aromatic plants (MAPs); however, there are little research studies about its effects on active ingredients of these plants. The aim of this research was to investigate the influence of low‐pressure cold plasma (LPCP) treatments (1, 3, and 5 min) on the essential oil (EO) content and composition of lemon verbena leaves. The EO content was determined using hydro‐distillation, and the composition of the extracted EOs was quantified using gas chromatography and gas chromatography–mass spectrometry techniques. The results showed that by increasing the LPCP treatment duration, the EO content was reduced from 1.2 to 0.9 (% v/w). The highest content of monoterpene hydrocarbons (e.g., limonene) and oxygenated sesquiterpenes (e.g., spathulenol and globulol) was also observed in LPCP‐treated ones, whereas the oxygenated monoterpenes (e.g., citral) content of control was measurably higher than those treated with LCPC. Abstract : Effect of cold plasma on quality of lemon verbena leaves was evaluated. By extending the LPCP treatment duration, EO content was decreased. The highest content of limonene was determined in LPCP‐treated ones.